2019
DOI: 10.2147/ijn.s211981
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dual targeting curcumin loaded alendronate-hyaluronan- octadecanoic acid micelles for improving osteosarcoma therapy</p>

Abstract: Introduction Curcumin (CUR) is a general ingredient of traditional Chinese medicine, which has potential antitumor effects. However, its use clinically has been limited due to its low aqueous solubility and bioavailability. In order to improve the therapeutic effect of CUR on osteosarcoma (i.e., bone cancer), a multifunctional micelle was developed here by combining active bone accumulating ability with tumor CD44 targeting capacity. Methods The CUR loaded micelles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Curcumin is a well-known potential anti-cancer drug but with poor bioavailability due to its low aqueous solubility and the body’s rapid metabolism and systemic elimination. In the past decade, multifunctional micelles, liposomal nanoparticles, and liposomes followed by 3D printed scaffolds in a controlled delivery of curcumin to osteosarcoma cells were developed to accumulate targeting capacity for improving the therapeutic effect [ 31 , 32 , 33 ]. Moreover, several curcumin analogs have been also developed to improve poor bioavailability for chemotherapy in various cancers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a well-known potential anti-cancer drug but with poor bioavailability due to its low aqueous solubility and the body’s rapid metabolism and systemic elimination. In the past decade, multifunctional micelles, liposomal nanoparticles, and liposomes followed by 3D printed scaffolds in a controlled delivery of curcumin to osteosarcoma cells were developed to accumulate targeting capacity for improving the therapeutic effect [ 31 , 32 , 33 ]. Moreover, several curcumin analogs have been also developed to improve poor bioavailability for chemotherapy in various cancers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…HA can target to CD44-overexpressed solid cancer and cancer stem cells, such as breast, lung, and prostate cancers. [23][24][25][26][27][28] By modifying hydrophobic segments, HA-derivatives could self-assemble into nanoparticles that could be used for chemotherapeutics delivery. 29,30 For instance, Jeannot et al reported HA-b-poly(γ-benzyl-L-glutamate) nanoparticles that could actively target to the CD44 receptor for delivery of vorinostat and gefitinib with strong tumor growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomicelles adhered to the bone because of the composition and released curcumin in a sustained manner. The cytotoxic effect of the nanostructures was pronounced [ 156 ]. Polymeric micelles are now being explored for photodynamic therapy by using potential photosensitizers for OSA.…”
Section: Nanomaterials For the Treatment Of Osamentioning
confidence: 99%